Persentase Karkas Ayam Kampung Super Umur 10 Minggu dengan Pemberian Ransum yang Mengandung Tepung Umbi Talas - Viktorinus jemanse Jemanse; Ni Ketut Sri Rukmini; Luh Suariani (GEMA AGRO, 2023)
Super free-range chicken is currently a very promising new business opportunity due to very high consumer demand. To support the demand for super free-range chicken meat, it is necessary to develop super free-range chicken farms in order to meet the increasing demand from year to year. The purpose of this study was to determine the effect of giving rations containing taro tuber flour on the carcass percentage of super free range chickens aged 10 weeks. This study used a completely randomized design (CRD) with 5 treatments and 3 replications. Each replication consisted of 5 chickens so that the number of chickens used was 75. The treatments were R0 control rations without taro tuber flour, R1 rations containing 5% taro tuber, R2 rations containing 10% taro tuber, R3 rations containing 15% taro tuber and R4 rations containing 20% ​​taro tuber. The results showed that the ingredients of taro tuber flour in the ration had a significant effect (P<0.05) on the slaughter weight and carcass weight of super free-range chicken, but did not have a significant effect (P>0.05) on the percentage of carcass and non-carcass percentage. . Giving 10% taro tuber flour (R2) produced the highest slaughter weight and carcass weight. The keywords are: Super Kampung Chicken and Taro Tuber Flou